An Amperometric Biosensor For Hg(II) Based On Urease/AlginateÃ¢â¬âChitosan Membrane Modified Screen Printed Carbon Electrode - Rochmad Kris Sanjaya; Nurul Ismillayli; Dhony Hermanto (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2019)
A screen-printed three-electrode system is fabricated to prepare a novel screen-printed biosensor for rapid determination of Hg(II) in aqueous solution. The amperometric biosensor is prepared by entrapping urease in alginateÃ¢â¬âchitosan membrane to modify the screen-printed carbon electrode. The urease/alginateÃ¢â¬âchitosan membrane for Hg(II) had optimum measurement conditions at work potential of -0.15 V, pH of 7, urea concentration of 75 mM, response time of 8 seconds, inhibition time of 7 minutes and temperature of 25 ÃÂ°C. The resulted biosensor characteristic were found to have the range concentration of Hg(II) ion between 40-90 ppb with the detection limit I10% was 66.45 ppb, the coefficient of variance (Cv) was 0.8%, and reactivation was 5 times reuse.